2015
DOI: 10.1097/md.0000000000002018
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statin Use and Open-angle Glaucoma in Hyperlipidemia Patients

Abstract: The aim of the study was to investigate the association between statin use and open-angle glaucoma (OAG) risk in hyperlipidemia patients.We used the research database of the Taiwan National Health Insurance program to conduct a population-based case-control study. A total of 1276 patients with newly diagnosed OAG were identified from 2004 to 2011. Controls comprised of 12,760 patients without glaucoma and were frequency-matched for age, sex, history of diabetes mellitus, and year of hyperlipidemia diagnosis at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 17 publications
7
38
0
4
Order By: Relevance
“…(), using data from the Taiwan National Health Insurance Database, demonstrated that the presence of OAG was associated with a higher prevalence of hyperlipidemia, and a more recently published paper, using the same database, showed an increased risk of OAG in subjects prescribed high doses of statin drugs (Chen et al. ). In agreement with findings from the Taiwan group, this study also demonstrated a positive association between hyperlipidemia and OAG with normal IOP, although the finding was significant only for low‐teen OAG in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(), using data from the Taiwan National Health Insurance Database, demonstrated that the presence of OAG was associated with a higher prevalence of hyperlipidemia, and a more recently published paper, using the same database, showed an increased risk of OAG in subjects prescribed high doses of statin drugs (Chen et al. ). In agreement with findings from the Taiwan group, this study also demonstrated a positive association between hyperlipidemia and OAG with normal IOP, although the finding was significant only for low‐teen OAG in the subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A further 6696 papers were also excluded following title and abstract review. Of the remaining 42 publications retained for further assessment and a full-text review, 15 papers were excluded for the following reasons: absence of a normal control (n ¼ 1) 17 ; hyperlipidemia or blood lipid level were not exposures (n¼8) [18][19][20][21][22][23][24][25] ; insufficient data to calculate the effect size (n¼5) [26][27][28][29][30] ; or glaucoma, IOP, or OHT were not outcomes (n ¼ 1). 31 The remaining 27 articles were included in this meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…In a prospective cohort study, Leung et al [4] reported that after adjusting for other confounding factors, patients with normal tension glaucoma had a reduced risk of visual field progression with the use of simvastatin, and the effect was independent of other systemic medications. In a cross-control study, Chen et al [5] reported that hyperlipidemia patients who use statins had the same risk of developing…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Recent research suggests that statins, which are medications used to lower cholesterol in patients with hyperlipidemia, may have some protection against glaucoma [3] , but it is still inconsistent on whether or not statins are beneficial in patients with glaucoma [2,4,5] .…”
Section: Disclosure Statementmentioning
confidence: 99%